2019
DOI: 10.1139/cjfas-2017-0504
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental conditions, population density, and prey type on the lipid content in Baltic herring (Clupea harengus membras) from the northern Baltic Sea

Abstract: Global climate change can affect the energy content of fish by altering their lipid physiology and consumption. We investigated the effects of different environmental stressors on the lipid content of the Baltic herring (Clupea harengus membras) from spawning ground samples that were collected annually in the northern Baltic Sea. During 1987–2014, the average lipid content of herring muscle decreased from 5%–6% (wet mass) to 1.5% (wet mass). Generalized linear mixed models indicated that sea water salinity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 54 publications
4
28
0
Order By: Relevance
“…Lipid content is the most contributing factor which correlates with PBDEs accumulation (Zeng et al 2013 ) and, although, the values reported in this study are in line with published data (Murray and Burt 2001 ; Rajasilta et al 2018 ), particular consideration should be taken when interpreting PBDEs concentrations in the light of the high natural variability of lipid content and the analytical method used (Nielsen et al 2005 ). It has been demonstrated that interannual variability of lipid could be in the range of 1.9% and 11.7%, with some Authors reporting a range between 1% and 25% (Nielsen et al, 2005 ; Rajasilta et al 2018 ). Therefore, it could be very beneficial to understand how the kinetic of bioaccumulations can vary in response to different seasonal lipid content, measured with a standardised protocols.…”
Section: Discussionsupporting
confidence: 87%
“…Lipid content is the most contributing factor which correlates with PBDEs accumulation (Zeng et al 2013 ) and, although, the values reported in this study are in line with published data (Murray and Burt 2001 ; Rajasilta et al 2018 ), particular consideration should be taken when interpreting PBDEs concentrations in the light of the high natural variability of lipid content and the analytical method used (Nielsen et al 2005 ). It has been demonstrated that interannual variability of lipid could be in the range of 1.9% and 11.7%, with some Authors reporting a range between 1% and 25% (Nielsen et al, 2005 ; Rajasilta et al 2018 ). Therefore, it could be very beneficial to understand how the kinetic of bioaccumulations can vary in response to different seasonal lipid content, measured with a standardised protocols.…”
Section: Discussionsupporting
confidence: 87%
“…However, a significant correlation has been identified between the abundance of P. minutes and the herring recruitment in the Gulf of Finland (Dippner et al, 2001). It seems that our findings support the conclusion of Rajasilta et al (2018) who argued that salinity acts as background signal that affects fish indirectly through changes in the prey community and fish diet. The trend of reducing salinity might continue into the future.…”
Section: Discussionsupporting
confidence: 82%
“…Finally, it should be noted that this study did not attempt to test the relationships between changes in environmental conditions and the physiological status in piscivores, mesopredators or food value in invertebrates. Lower salinity (as well as increasing herring population size) has been associated to reduced lipid content in Baltic herring during the same time period as studied here, due to the more energetically costly osmoregulation with decreasing salinities (Rajasilta et al 2019). Casini et al (2016) discuss potential negative effects on low oxygen concentrations for physiological status in cod, which is also a factor relevant for the benthic invertebrate Saduria, and an increasing environmental concern in the Baltic Sea (Carstensen et al 2014).…”
Section: Discussionmentioning
confidence: 56%
“…In forage fish, such as sprat and herring, the lipid content is on average 34% of the body mass, and females with higher lipid content have higher egg survival (Laine and Rajasilta 1999). Previous studies have seen that lipid content and blubber thickness are influenced by prey quality (Røjbek et al 2014;Kauhala et al 2017;Rajasilta et al 2019), while body size in fish also responds to sizeselective predation (e.g. Vainikka et al 2009).…”
Section: Introductionmentioning
confidence: 99%